A biomass carbon mass coated with modified TiO2 nanotube/graphene for photocatalysis. (5th May 2017) - Lian, Yiren; Zhu, Wenkun; Yao, Weitang; Yi, Huan; Hu, Zuowen; Duan, Tao; Cheng, Wencai; Wei, Xianfeng; Hu, Guozhen
Abstract : A floating mass constructed with fungus and Fe/N-TNTs/NG for the photocatalysis on the surface of solution. Abstract : Powdered modified TiO2 materials are commonly used for photocatalysis. They are easily dispersed in solution but difficult to recycle. In addition, the low light transmission and lack of oxygen in solution also cause a decrease of the photocatalytic efficiency for practical applications. Here we prepare a low-density circular slice which can be suspended on the surface of an aqueous solution and can be used to enrich methylene blue easily. The body of the circular slice is a kind of biomass carbon derived from fungus while the surface of the circular slice is coated with Fe/N co-doped TiO2 nanotubes and a N-doped graphene composite. The advantages are that the circular slice cannot only be convenient to recycle, but also be easy to receive light and oxygen. According to the photocatalytic activity test, the floatable material consisting of Fe/N-TNTs/NG and fungus shows superb performance on the degradation of methylene blue under simulated solar irradiation, which makes it a promising photocatalytic material.